Promoting Compassionate Responses to Disclosures of Sexual Violence in University Settings: Exploring the Impact of a Social Marketing Campaign - Irvine-Collins, Emma (Violence against women, 2023)
This study explores a social marketing campaign aimed to promote compassionate responses to disclosures of sexual violence from peers and raise awareness of university-based formal support services. Findings from a survey (n = 189) and follow-up focus groups (n = 11) conducted with university students in Australia indicated that exposure to the campaign may support students’ self-perceived confidence in responding compassionately to disclosures of sexual violence and raise awareness of university-based formal support services. These findings suggest social marketing may be a useful tool to form part of universities’ sexual violence response and prevention strategies. These findings may help inform future university campaigns.